EQUAL Cryptococcus Score 2018: A European Confederation of Medical Mycology Score Derived From Current Guidelines to Measure QUALity of Clinical Cryptococcosis Management. (12th November 2018) - Spec, Andrej; Mejia-Chew, Carlos; Powderly, William G; Cornely, Oliver A
Abstract: Cryptococcocis is an opportunistic fungal infection with high morbidity and mortality. Guidelines to aid clinicians regarding diagnosis, management, and treatment can be extensive and challenging to comply with. There is no tool to measure guideline adherence. To create such a tool, we reviewed current guidelines from the Infectious Diseases Society of America, the World Health Organization, the American Society of Transplantation, and recent significant publications to select the strongest recommendations as vital components of our scoring tool. Items included diagnostic tests (blood, tissue, and cerebrospinal fluid cultures, Cryptococcus antigen, India ink, histopathology with special fungal stains, central nervous system imaging), pharmacological (amphotericin B, flucytosine, azoles) and nonpharmacological treatments (intracranial pressure management, immunomodulation, infectious disease consultation), and follow-up of central nervous system complications. The EQUAL Cryptococcus Score 2018 weighs and aggregates the recommendations for the optimal management of cryptococcosis. Providing a tool that could measure guideline adherence or facilitate clinical decision-making.